FORMULATION OF FOOD BAR BASED ON BANANA, OAT, AND SPINACH FLOUR AS A SOURCE FIBER SNACK FOR DASH DIET (DIETARY APPROACHES TO STOP HYPERTENSION) - Annisa Inas Ariyanti; Hidayah Dwiyanti; Teguh Jati Prasetyo (Journal of Global Nutrition, 2022)
The prevalence of high blood pressure (hypertension) in Indonesia has increased. One of the best dietary recommendations for people with hypertension is Dietary Approaches to Stop Hypertension (DASH). Various product innovations have been developed to support the implementation of the DASH diet, one of them is a food bar. Potential ingredients that support the diet are banana, oat, and spinach. In addition to containing high fiber and potassium, these three ingredients are also low in sodium, so they are good for heart health. This study aims to determine the formulation of a food bar that has an acceptable sensory characteristic and high fiber content. The research design was non-factorial experimental study using a randomized block design (RAK). The treatment that was tried was the proportion of raja banana : composite flour (oat : spinach flour = 1 : 3) consisting of 4 formulas: P1 (90%:10%), P2 (85%:15%), P3 (80%:20%), and P4 (75%:25%). The result was analyzed using SPSS software. Proportion of banana with composite flour has a significant effect on the results of hedonic variables (taste, aroma, flavor, overall) and hedonic quality (texture quality, color quality, taste quality, aroma quality, flavor quality). The highest fiber content was found in the product formula P4 (3.8g/100g), while the lowest food fiber content was in the food bar formula P1 (1.57g/100g). The result of Effectiveness Index to determine the best formula was P1. The higher amount of composite flour, the lower sensory value of the food bar. However, the higher amount of composite flour, the higher dietary fiber content in the food bar.